Преобразовать в произведение:tg^4 x - 4tg^2 x + 3

0 голосов
43 просмотров
Преобразовать в произведение:
tg^4 x - 4tg^2 x + 3

Алгебра (20 баллов) | 43 просмотров
Дано ответов: 2
0 голосов
Правильный ответ

Tg ^2 X = A 
A^2 - 4A + 3 = ( A - 1 )*( A - 3)
D = 16 - 4*1*3 = 16 - 12 = 4
V D = 2
A1 = ( 4 + 2 ) : 2 = 3 
A2 = 2 : 2 = 1 
.............................................
Tg^4X - 4Tg^2X + 3 = ( Tg^2X - 1)*( Tg^2X - 3 ) = ( TgX - 1)*( TgX + 1)*( TgX - V3)*(TgX + V3 ) 

0 голосов
tg^4 x - 4tg^2 x + 3=(tg^2-3)(tg^2-1)=(tg-√3)(tg +√3)(tg-1)(tg+1)
(317k баллов)